2022
DOI: 10.1088/1755-1315/1001/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the income of organic shallot farmers in Boyolali Regency

Abstract: The consumption of organic products has become a new trend that is more environmentally friendly, healthy, and at better prices advantageous for farmers. Furthermore, organic farming reduces the greenhouse effect and global warming by absorbing carbon into the soil. This study aimed to determine the income factors of organic shallot farming and the cultivation efficiency in Boyolali Regency using the descriptive method. A simple random sampling technique was used to obtain the sample, consisting of organic sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This result can be seen in table two, where farmers use many pesticides to cultivate garlic and shallots. Farmers feel they can take action to handle pests and diseases on their land and feel that they have no difficulty in controlling these pests (Suswadi & Prasetyo, 2022). Human resources who know pest control make them not concerned about intercropping or not, so that intercropping decisions are not affected by pest control choices due to changes in micro seasons.…”
Section: Resultsmentioning
confidence: 99%
“…This result can be seen in table two, where farmers use many pesticides to cultivate garlic and shallots. Farmers feel they can take action to handle pests and diseases on their land and feel that they have no difficulty in controlling these pests (Suswadi & Prasetyo, 2022). Human resources who know pest control make them not concerned about intercropping or not, so that intercropping decisions are not affected by pest control choices due to changes in micro seasons.…”
Section: Resultsmentioning
confidence: 99%
“…Without a healthy soil, the crop production is dependent on chemical fertilizers. Today, after the COVID-19 pandemic and within the war in Ukraine, humankind has found that the need to reduce the use of chemical fertilizers and to protect the health of the soils is also a strategy to achieve safe food production [54]. We propose to extend the use of cover crops in vineyards to reduce soil losses.…”
Section: Further Researchmentioning
confidence: 99%
“…Factors that influence the behavior of farmers in the use of pesticides are education and knowledge of farmers about the agricultural system [23]. Excessive use of liquid pesticides and not in accordance with recommendations can result in residues on shallots that can harm consumers [24].…”
Section: Efficiency Of Production Factorsmentioning
confidence: 99%